2021
DOI: 10.1002/anie.202106718
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Engineering the Stereoselectivity of Humulene Synthase

Abstract: The non‐canonical terpene cyclase AsR6 is responsible for the formation of 2E,6E,9E‐humulene during the biosynthesis of the tropolone sesquiterpenoid (TS) xenovulene A. The structures of unliganded AsR6 and of AsR6 in complex with an in crystallo cyclized reaction product and thiolodiphosphate reveal a new farnesyl diphosphate binding motif that comprises a unique binuclear Mg2+‐cluster and an essential K289 residue that is conserved in all humulene synthases involved in TS formation. Structure‐based site‐dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…Successful interconversion of catalytic specificities between AhCS and AhIS was obtained based on the structure‐guided mutagenesis, probing the three active site residues [L311‐S419‐C458]/[M311‐V419‐A458] that governed the divergent C3/C6 reprotonation of GA. Previous studies reported a single residue control of the cyclization reactions at earlier steps, such as the isomerization of FPP, [11a] and the initial 1,10‐cyclization or 1,11‐cyclization [24] . In the present study, we revealed that three active sites act in concert to control the distinct C3/C6 reprotonation regioselectivity of GA in the deprotonation‐reprotonation process, resulting in different and complex skeletons.…”
Section: Discussionsupporting
confidence: 55%
“…Successful interconversion of catalytic specificities between AhCS and AhIS was obtained based on the structure‐guided mutagenesis, probing the three active site residues [L311‐S419‐C458]/[M311‐V419‐A458] that governed the divergent C3/C6 reprotonation of GA. Previous studies reported a single residue control of the cyclization reactions at earlier steps, such as the isomerization of FPP, [11a] and the initial 1,10‐cyclization or 1,11‐cyclization [24] . In the present study, we revealed that three active sites act in concert to control the distinct C3/C6 reprotonation regioselectivity of GA in the deprotonation‐reprotonation process, resulting in different and complex skeletons.…”
Section: Discussionsupporting
confidence: 55%
“…33 In contrast, for the sesquiterpene precursor a direct 1,10-cyclisation to the ( E , E )-germacradienyl cation ( 5 ) or a 1,11-cyclisation to the ( E , E )-humulyl cation ( 6 ) are possible. 34,35 For 1,6- and 1,7-cyclisations to the bisabolyl cation ( 9 ) or the cycloheptenyl cation ( 10 ) again first an isomerisation to nerolidyl diphosphate (NPP) is required, allowing rotation around the C2–C3 single bond. 34 NPP can also react by 1,10-cyclisation to the ( Z , E )-germacradienyl cation ( 7 ) or by 1,11-cyclisation ( Z , E )-humulyl cation ( 8 ).…”
Section: Terpenoid Biosynthesis and Structural Diversitymentioning
confidence: 99%
“…34 NPP can also react by 1,10-cyclisation to the ( Z , E )-germacradienyl cation ( 7 ) or by 1,11-cyclisation ( Z , E )-humulyl cation ( 8 ). 35,36 For the larger terpene precursors GGPP and GFPP the number of possible cyclisation modes is further increased, but the general principles remain the same: for 1,6- and 1,7-cyclisations the isomerisation by allylic transposition of diphosphate from C1 to C3 is mandatory, while for all larger rings this step is optional, but can explain the introduction of Z -configured double bonds in the biosynthetically last introduced terpene unit.…”
Section: Terpenoid Biosynthesis and Structural Diversitymentioning
confidence: 99%
“…L285 extends into the active pocket of AsR6, which is likely involved in product stereoselectivity. M261 may be implicated in the initial conversion of FPP into NPP …”
Section: Application Of Site-directed Mutagenesis In Stssmentioning
confidence: 98%